Assessment of psychiatric morbidity and quality of life in children and adolescents with cutaneous leishmaniasis and their parents - Turan, Enver; Kandemir, Hasan; Yeşilova, Yavuz; Ekinci, Suat; Tanrıkulu, Osman; Kandemir, Sultan Basmacı; Gurel, Mehmet Salih (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Cutaneous leishmaniasis (CL) is a common parasitic infectious disease caused by different species of the leishmania genus. The skin lesions are usually found on exposed areas, especially the face, arms and legs. Although the disease does not cause significant morbidity, the lesions can be troublesome and unsightly. The disease have negative impacts in areas such as patients’ psychological well-being, social life and daily activities in adults. Aim : To determine the frequency of psychiatric morbidity in children and adolescents who have cutaneous leishmaniasis (CL) and to determine the effect of CL on their levels of depression and anxiety and on their quality of life (QoL). Material and methods : Fifty-four patients with CL (29 males and 25 females), who were 7 to 18 years of age, were assessed with the Child Depression Inventory (CDI) and the State-Trait Anxiety Inventories for Children (STAIC). The patients and their mothers were assessed with the Pediatric Quality of Life Inventory Parent and Child Versions (PedQL-P and C, respectively). This questionnaires were filled in by the control group consisting of 40 healthy children and adolescents (20 males and 20 females) and their parents from the local community matched for age, gender, and education level of the parents. Results : Both the patient group and the control group had high scores on the depression measurement scale (t = 5.36, p < 0.05). These measurements also show significant differences between children and adolescents, who were defined as 12 years of age and under as well as older than 12 years, respectively (12 years of age and under (t = 3.14, p = 0.04); over 12 years (t = 5.37, p < 0.001)). However, there was no significant difference between the anxiety scores of the general patient group and the control group when classified according to age. The anxiety sensitivity index scores did not differ in either group from those of the control group. The patients’ and the mothers’ QoL scores for all of the scales, including all subscale scores, were significantly different from those of the control group (both 12 years of age and under as well as older than 12 years). Conclusions : The results have shown that the frequency of depressive symptoms is much higher in patients who have CL than in healthy controls. In addition, the QoL of children and adolescents with CL and of their mothers was found to be much lower than that of the control group. Therefore, the follow-up for patients with CL who are referred to dermatology clinics should include a psychiatric evaluation. If necessary, they should be referred for psychiatric support.